(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
The article presents a brief research conducted among the Venetic pottery for daily use in the early Padua. Between the sixth and fourth centuries B.C. a simple form of a small local olla recurs punctually, with its peculiar characters, among the urban remains, in grave goods and in votive deposits as of hegemonic center as of smaller centers in the oriental Veneto where the Paduan influence spread. Their importance appears to be connected to the routes of trade to the north and east. Finally, the distribution, the diffusion of this olla and its links with the ceramics of the Bronze Age, offers useful evidence about ancient people’s attention to preserve a tradition, while indicating between human groups a common cultural identity.